Muhammadiyah's View of the Pancasila State in the Dynamics of Diversity in Indonesia after the 2015 Congress - Muhammad Lukman Hakim; David Efendi; Alam Mahadika (International Journal of Social Science and Religion (IJSSR), 2020)
Indonesia is a multiculturalist country by placing Pancasila as the main milestone in formulating all attitudes towards the nation and state, which are expected to inherit a nation's noble and noble culture. Pancasila contains values ​​that are very noble and do not conflict with religious and social values. The motto "Different but still one" unites differences in religion, race, ethnicity, and culture, from Sabang to Merauke. So that in the future, it will prevent Indonesia from various threats that damage the nation's sovereignty, such as separatism, treason, terrorism, and national diseases that can erode the joints of the state later. Muhammadiyah is an important part of the nation, one of which has a role in participating in caring for and preserving this noble and noble culture of the country. With various contributions in the field of thought, such as the "Pancasila State" as a progressive Indonesian as Darul Ahdi wa al-Syahadah, progressing Islam, Insha Allah will be able to nurture the noble values ​​of Pancasila.